Pendidikan Karakter Berbasis Ngaji Rasa di Pesantren Salaf dan Implikasinya terhadap Penguatan Pembelajaran PAI - Batula, Abu Warasy; Fakhruddin, Agus; Faqihuddin, Achmad (Fakultas Agama Islam, 2026)
This study aims to explore spirituality-based character education through theNgaji Rasa program in salaf Islamic boarding schools and its implications forstrengthening Islamic Religious Education (PAI) in formal schools. Using aqualitative method with a case study approach at the Azziyadah Islamic BoardingSchool, data was collected through in-depth interviews, participatory observation,and documentation studies. The results reveal that Ngaji Rasa is implementedthrough four main pillars: direct learning, religious tourism, creative economicempowerment, and respect for the kiai. Through this ecosystem, santri internalizeessential character values such as obedience, patience, sincerity, responsibility,and tazkiyatun nafs or purification of the soul. The findings show that Ngaji Rasafunctions as experiential moral education that balances the dimensions of dzikir(spiritual), fikir (rational), and amal (practical action). The implications for PAI informal schools include the need for a paradigm shift towards a holistic approachthat integrates cognitive, affective, and psychomotor aspects. This studyrecommends strengthening the role of teachers as spiritual role models (murabbi)and implementing experience-based learning to overcome the moral crisis of theyounger generation. The integration of the inner values of Islamic boardingschools is expected to create more meaningful and transformative PAI learningfor students' character in the contemporary era.